STUDI PERILAKU KONSUMEN: FAKTOR INTERNAL DAN TEKANAN SOSIAL TERHADAP MINAT BELI MEREK GLOBAL SENSITIF - Mouren Ghina Deswita; Nurist Surayya Ulfa (Interaksi Online, 2026)
This research investigates the impact of consumer resentment, brand image perception, social influence, and consumer attitude on the willingness to buy boycott-targeted global brands within Indonesia's food and beverage sector. The analysis captures the post-boycott cool-down period, characterized by declining public emotional intensity alongside unrecovered purchasing levels. Utilizing an online survey of 200 Indonesian Generation Z respondents, data were processed via multiple linear regression using SPSS. Simultaneous testing confirms that all four determinants significantly dictate buying propensity. Individually, however, only social influence exerts a significant effect. These insights demonstrate that interpersonal pressure from the immediate environment serves as the primary driver suppressing consumer buying willingness toward brands linked to international humanitarian crises.